Microsurgical vs. Endoscopic Excision of Colloid Cysts: An Analysis of Complications and Costs Using a Longitudinal Administrative Database - Connolly, Ian David; Johnson, Eli; Lamsam, Layton; Veeravagu, Anand; Ratliff, John; Li, Gordon (Frontiers in Neurology, 2017)
Objective: Open microsurgical and endoscopic approaches are the two main surgical options for excision of colloid cysts. Controversy remains as to which is superior. Previous studies consist of small cohort sizes. This topic has not been investigated using national administrative claims data which benefits from larger patient numbers. Methods: Current Procedural Terminology (CPT) and International Classification of Disease version 9 (ICD-9) coding at inpatient visit was used to select for index surgical procedures corresponding to microsurgical or endoscopic excision of colloid cysts. Comorbidities, costs, and complications were collected. Results: We identified a total of 483 patients. 240 were from the microsurgical cohort and 243 were from the endoscopic cohort. The two groups displayed similar demographic and comorbidity profiles. Thirty-day post-operative complications were also similar between groups with the exception of seizures and thirty-day readmissions, both higher in the open surgical cohort. The seizure rates were 14.7% and 5.4% in the microsurgical and endoscopic cohorts respectively (p = 0.0011). The thirty-day readmission rates were 17.3% and 9.6% in the microsurgical and endoscopic cohorts respectively (p = 0.0149). Index admission costs and 90-day post discharge payments were higher in patients receiving microsurgical excision. Conclusions: An analysis of administrative claims data revealed few differences in surgical complications following colloid cyst excision via microsurgical and endoscopic approaches. Post-operative seizures and thirty-day readmissions were seen at higher frequency in patients who underwent microsurgical resection. Despite similar complication profiles, patients undergoing microsurgical excision experienced higher index admission costs and 90-day aggregated costs suggesting that complications may have been more severe in this group.